An Virtual Education System for Rural - Pandey, Mohit; Sankhyadhar, Shubhanghi (International Journal of Computer Sciences and Engineering, 2025)
In the modern era, computer has become urgency. The use of computer is expanding with such an extent that the life without the computer is unimaginable. Nevertheless the roots of computer have emerged in each and every age group and sector still there are some areas where the computers cannot be used with such a proficiency. The people of rural areas are unable to get the sound knowledge of various things due to the unavailability of the resources in their areas. Our research work focuses on imparting the knowledge to the rural areas using the concept of the far-flung technology, i.e., cloud computing.